Anthropometric profile and serum 25-hydroxyvitamin D3 levels in elite soccer players - Pietraszewska, J.; Burdukiewicz, A.; Zagrodna, A.; Stachon, A.; Andrzejewska, J. (South African Journal for Research in Sport, Physical Education and Recreation, 2019)
The objective of the study was to investigate serum vitamin D concentration in a sample of elite soccer players and to analyse the relationship between body composition and anthropometric variables and 25(OH)D3 status. Research data was collected by measuring 29 Polish Football Premier League players, native to Poland. Anthropometric and biochemical data were collected in December. Mean body height is similar to that of world elite soccer players. Trunk, lower, and upper extremity girths measured indicate a well-developed musculature. Body composition analysis identified a mean fat percentage of 18±3.0%. A high prevalence of vitamin D deficiency was observed in the sample. Mean serum 25(OH)D3 concentration for the group was 18.3±4.4ng/mL. Significant positive correlations between 25(OH)D3 and anthropometric variables characterising body musculature and skeletal size may show the indirect impact of vitamin D on the development and function of these respective systems.